Estimated Pulse Wave Velocity Is Associated With All‐Cause Mortality and Cardiovascular Mortality Among Adults With Chronic Kidney Disease - Xiao‐Hua Feng; Yi Chen; Xue‐Qi Chen; Wei‐Hong Zhao (The Journal of Clinical Hypertension)
ABSTRACT This study aimed to assess the correlation between estimated pulse wave velocity (ePWV) and mortality rates related to all‐cause and cardiovascular disease (CVD) among individuals diagnosed with chronic kidney disease (CKD) in the United States. A total of 4669 participants with CKD were identified from the National Health and Nutrition Examination Survey conducted between 1999 and 2018. We calculated the incidence of CKD using an estimated glomerular filtration rate (eGFR) of < 60 mL/min/1.73 m2. Our study examined the association between ePWV and mortality risk based on weighted Kaplan–Meier plots and multivariate Cox regression. Linear testing between ePWV and mortality from all causes and CVD was performed using restricted cubic splines and Cox regression. This study included 4669 patients with CKD from the NHANES, representing 37 million Americans with CKD. There was a mean age of 71.9 years, and 48.1% of participants were male. With every increase of 1 m/s in ePWV measurement, there is a corresponding 31% (hazard ratio [HR]: 1.31, 95% confidence interval [CI]: 1.28–1.34) increase in the rate of mortality from all causes and a 32% (HR: 1.32, 95% CI: 1.27–1.37) increase in the rate of mortality from CVD. A significantly higher rate of cardiovascular and all‐cause mortality was observed in patients with CKD with elevated ePWV than in those with lower ePWV, as shown in the weighted Kaplan–Meier plots. Patients with CKD have a significant relationship between ePWV and all‐cause and cardiovascular mortality.